2014
DOI: 10.5056/jnm14052
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Halitosis Diagnosed by a Questionnaire and Halimeter and Symptoms of Gastroesophageal Reflux Disease

Abstract: Background/Aims The relationship between halitosis and gastroesophageal reflux disease (GERD) remains controversial. The aim of this study was to investigate an association between subjective and objective halitosis and GERD. Methods The subjects were enrolled from participants who visited a health promotion center at Seoul National University Bundang Hospital. For diagnosis of halitosis, a questionnaire was requested, and volatile sulfur compounds (VSCs) were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The prevalence of halitosis varies according to the study population, because the perception of halitosis differs among culturally diverse populations [4] . In Japan, population-based studies have reported the prevalence of halitosis to be 6–23% [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of halitosis varies according to the study population, because the perception of halitosis differs among culturally diverse populations [4] . In Japan, population-based studies have reported the prevalence of halitosis to be 6–23% [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…1,8,16,[93][94][95] Whether extra-esophageal reflux symptoms are truly related to esophageal reflux remains controversial. A recent study has shown that the presence of reflux symptoms is related to significantly higher levels of TRPV1, PAR2, and IL-8.…”
Section: Symptomsmentioning
confidence: 99%
“…Bien que la recherche de H. pylori n’a pas été faite chez tous nos patients (absence de moyens financiers), nos résultats ont montré une forte fréquence de l’infection au cours de l’halitose (sur 10 patients atteints d’halitose dépistés pour l’infection à H. pylori , 90% étaient porteurs de la bactérie), confortant ainsi le lien supposé entre H. pylori et l’halitose retrouvé dans la littérature [10, 21-23]. Mais les études existantes montrent des résultats contradictoires; pour d´autres études l´halitose serait liée aux maladies du TGI autres que l´infection à H. pylori [20,24]. Moshkowitz et al ont en effet rapporté une forte association entre la survenue et la sévérité de l’halitose avec le reflux gastro-œsophagien (RGO) [20] et l’absence de lien entre d’autres facteurs de troubles dyspeptiques tels l’ulcère peptique ou l’infection à H. pylori et l’halitose [20, 25].…”
Section: Discussionunclassified